2007
DOI: 10.1143/jjap.46.l465
|View full text |Cite
|
Sign up to set email alerts
|

Strong White Photoluminescence from Carbon-Incorporated Silicon Oxide Fabricated by Preferential Oxidation of Silicon in Nano-Structured Si:C Layer

Abstract: A new approach to development of light-emitting SiO 2 :C layers on Si wafer is demonstrated. Carbon-incorporated silicon oxide was fabricated by three-step procedure: (1) formation of the porous silicon (por-Si) layer by ordinary anodization in HF:ethanol solution; (2) carbonization at 1000 C in acetylene flow (formation of por-Si:C layer); (3) oxidation in the flow of moisturized argon at 800 C (formation of SiO 2 :C layer). Resulting SiO 2 :C layer exhibited very strong and stable white photoluminescence at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…12,14) The PL intensity of SiOC seems to increase with surface area, as suggested by some reports that PL origins might be at the interface between carbon and silica. 12,14) Recently, we have found that mesoporous carbon-silica (MPCS) 13,15,16) that has a large surface area emits a strong white PL. In our previous studies, we found that PL intensity depends on hydrolysis and polycondensation reactions in the sol-gel method for preparing MPCS.…”
Section: Introductionmentioning
confidence: 79%
“…12,14) The PL intensity of SiOC seems to increase with surface area, as suggested by some reports that PL origins might be at the interface between carbon and silica. 12,14) Recently, we have found that mesoporous carbon-silica (MPCS) 13,15,16) that has a large surface area emits a strong white PL. In our previous studies, we found that PL intensity depends on hydrolysis and polycondensation reactions in the sol-gel method for preparing MPCS.…”
Section: Introductionmentioning
confidence: 79%
“…Recently, it has been demonstrated that carbon incorporated silicon oxide nanostructured materials exhibit a strong white photoluminescence (PL). Intriguing is that white PL was demonstrated by SiOC materials fabricated by quite different methods, namely: SiOC thin films deposited by thermal chemical vapor deposition (TCVD) [1], atmospheric pressure microplasma jet deposition [2], magnetron sputtering deposition [3], C + implantation into SiO 2 [4][5][6], chemical vapor deposition technique [7], carbonization/oxidation of porous silicon [8,9], sol-gel method [10].…”
Section: Introductionmentioning
confidence: 99%
“…Various fabrication methods of carbon incorporated silica were demonstrated [1,2] by several researchers. Recently, we reported oxidized mesoporous carbon-silica (MPCS) emits white PL and pointed out that light emitting function might be related to carbon-silica chemical bonding state and transmittance [3].…”
Section: Introductionmentioning
confidence: 99%